1996
DOI: 10.1007/bf02716814
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary gonadotropins regulate spermatogonial differentiation and proliferation in the rat‡

Abstract: The relative regulatory roles of the pituitary gonadotropins, luteinizing hormone and follicle stimulating hormone in the spermatogonial proliferation has been studied using specific antibodies against these hormones in the immature rats. Immunoneutralization of luteinizing hormone for 7 days resulted in significant reduction in tetraploid cells and total absence of haploid cells, while there was a relative increase in the diploid population. This was also accomopanied by a decrease in spermatogonial prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Similar results were also obtained with FSH receptor antibodies which caused the germ cell apoptosis (Dighe et al, unpublished observations) or reduction in the fertility [9]. Intriguingly, immunoneutralization of gonadotropins did not cause apoptosis of the spermatogonial population, but caused a decrease in their proliferation [10]. Thus, it appears that blocking of two gonadotropins differently affected different germ cells.…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…Similar results were also obtained with FSH receptor antibodies which caused the germ cell apoptosis (Dighe et al, unpublished observations) or reduction in the fertility [9]. Intriguingly, immunoneutralization of gonadotropins did not cause apoptosis of the spermatogonial population, but caused a decrease in their proliferation [10]. Thus, it appears that blocking of two gonadotropins differently affected different germ cells.…”
Section: Introductionsupporting
confidence: 76%
“…This recovery is probably due resurgence of spermatogenesis from the beginning with spermatogonial proliferation. Earlier data from the laboratory had clearly shown that immunoneutralization of gonadotropins does not cause apoptosis of spermatogonial population, but there was significant reduction in the rate of proliferation of these cells [10]. Restoration of spermatogenesis in hypo-gonadotropin patients by gonadotropin treatment is also probably due to initiation of spermatogenesis at the mitotic phase.…”
Section: Discussionmentioning
confidence: 97%
“…Since FSH and testosterone are proximally required by stertoll cell to support spermatogenesis (Carr and Griffin, 1992). They act synergistically, and influence the different steps of sperm cells, transformation during spermatogenesis (Shetty et al 1996). Depletion in the biosynthesis of these hormones due to external androgen could block spermatogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that the arrest of spermatogenesis is due to the reduced activity of Leydig cells (Kasturi et al, 1995). FSH plays a major role in transformation and maturation of round to elongated spermatid (Moudgal & Suresh, 1995;Shetty et al, 1996).…”
Section: Discussionmentioning
confidence: 99%